Application properties of starches extracted from underground starchy crops of South American origin - Pascoli Cereda, Marney [UNESP] (Elsevier, 2022)
The application properties of starches are more common in industrial use than in research application where starch properties are mostly concerned. This chapter aims to guide the reader on the evolution of various parameters used to measure these properties of starch. Among others, this chapter conceptualizes and highlights viscosity as the most important application property. To measure viscosity, the RVA is the mostly used device for research, but we suggest some more simple equipment for industries, as Ford cup and Brookfield. The DSC provided more reliable results of temperatures involved in the gelatinization process. The author highlights the occurrence of complexation of amylose with phenolic compounds and possible arrangements with mucilage, as factors capable of influencing the properties of starches extracted from underground raw materials.
Keywords: color; gelatinization; mucilage; paste properties; phenols; transparency; Viscosity